Prostate-specific antigen velocity as a predictor of survival outcomes in patients with prostate cancer: a meta-analysis - Cui, Feilun; Zhang, Yueshi; Liu, Ziyan; Zhou, Yongjing; Man, Changfeng; Fan, Yu (Frontiers in Oncology, 2026)
BackgroundProstate-specific antigen velocity (PSAV) has emerged as a promising biomarker for predicting survival outcomes in prostate cancer patients.ObjectivesTo assess the association between PSAV and both all-cause mortality and prostate cancer-specific mortality (PCSM) in men diagnosed with prostate cancer by conducting a meta-analysis.MethodsA comprehensive search of electronic medical databases, including PubMed, Web of Science, and Embase, was conducted to identify relevant studies published up to March 1, 2025. Studies reporting adjusted hazard ratios (HR) with 95% confidence intervals (CI) for survival outcomes in prostate cancer patients, based on categorical analyses of PSAV, were included. Pooled HRs with 95% CI was calculated using random-effects models to account for clinical heterogeneity across studies.ResultEleven studies involving 3,713 prostate cancer patients were identified and analyzed. The meta-analysis revealed that elevated PSAV was associated with a higher risk of both all-cause mortality (HR 1.96; 95% CI 1.33–2.88) and PCSM (HR 5.38; 95% CI 2.76–10.51). In stratified analyses, the pooled HR for all-cause mortality was 1.91 (95% CI 1.43–2.55) among patients with localized prostate cancer, compared to 1.26 (95% CI 0.41–3.84) in those with metastatic disease.ConclusionsElevated PSAV is a significant predictor of all-cause mortality and PCSM in prostate cancer patients. Measuring PSAV has the potential to improve the prediction of survival outcomes in this population. However, further research is needed to standardize PSAV measurement and validate its predictive value across diverse patient groups. Systematic review registration.